REVITALISASI KAWASAN PEMUKIMAN PESISIR DESA KATIALADA KABUPATEN GORONTALO UTARA - Eka, Rahmawati; Moidady, Ayu Hirabayasih; Dokliwan, Sultan A. Malik G.S. (Universitas Bina Taruna Gorontalo, 2024)
Abstract: Revitalization of the Katialada Village Coastal Settlement Area This research aims to revitalize coastal residential areas. The research method uses descriptive qualitative, namely by means of a field survey which aims to obtain factual information about the condition of coastal residential areas in Kwandang District, North Gorontalo Regency. Field surveys were conducted at locations in North Gorontalo Regency in November – December 2023, starting with initial data collection followed by semi-structured interviews, observations, and data confirmation with the reality in the field and the views of village officials, local communities and hamlet heads. The results of the research show that (1) Katialada Village settlements have the characteristics of around 75% stilt houses, especially in mangrove hamlets (2) The main livelihood of the people in this village is mostly fishermen. The conclusion from the research conducted is that coastal settlements tend to have a negative impact resulting in coastal settlement areas having problems such as flooding, rubbish, inadequate infrastructure, so there is a need for a harmonious integration process in developing coastal areas. Moreover, the Katialada village area has great potential to be developed, such as the beauty of the mangrove area which can be used as a tourist spot, as well as infrastructure that can support the results of fishermen because the great potential of Katialada village is marine products so that it can improve the regional and community economy.